Enhancing battery performance with nanofluid electrolytes - Samylingam, Lingenthiran; Aslfattahi, Navid; Kadirgama, Kumaran; Veerendra Babu, Arigela Sri Satya; Kok, Chee Kuang; Norazlianie, Sazali; Wan Sharuzi, Wan Harun; Liew, Kia Wai (Semarak Ilmu Publishing, 2025)
The expeditious advancement of energy storage technologies, namely in the domain of batteries, has significant importance in addressing the escalating need for portable electronic devices, electric automobiles, and renewable energy systems. The utilizationof nanofluid electrolytes is a possible option for enhancing battery performance. Nanofluids, which are colloidal suspensions consisting of nanoparticles dispersed in a base electrolyte, present a distinct prospect for augmenting the fundamental characteristics of battery systems. This review paper investigates the potential of nanofluid electrolytes to significantly transform battery technology. The dispersion of nanoparticles inside the electrolyte has exhibited notable advantages in temperature regulation, ion conduction, and the longevity of cycles. Our objective is to gain a comprehensive understanding of the fundamental processes involved in the interaction between nanoparticles and electrolytes. Nanofluid electrolytes offer notable benefits, such as enhanced heat dissipation capabilities, hence effectively addressing concerns related to thermal runaway risks and significantly prolonging the operational lifespan of batteries. Furthermore, the increased efficiency of ion transport in batteries can be attributed to the nanoparticles' elevated surface area and distinctive surface chemistry, resulting in higher energy and power densities. This research additionally examines the obstacles and potential of incorporating nanofluid electrolytes into existing commercial battery technology. Although showing potential, additional research and development efforts are needed to investigate the synthesis, stability, and scalability of battery components based on nanofluids. In summary, it can be concluded that the utilization of nanofluid electrolytes holds significant potential to enhance battery efficiency by effectively tackling the issues related to heat regulation and ion conduction. The utilization of nanofluids in batteries can significantly transform the energystorage domain and expedite the shift toward a more sustainable and electrified future.